If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 5x + -3 Reorder the terms: 2 = -3 + 5x Solving 2 = -3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + -5x = -3 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + -5x = -3 + 0 2 + -5x = -3 Add '-2' to each side of the equation. 2 + -2 + -5x = -3 + -2 Combine like terms: 2 + -2 = 0 0 + -5x = -3 + -2 -5x = -3 + -2 Combine like terms: -3 + -2 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 3.85=5.47 | | 3.85=5.4 | | -4x-6=-30 | | 9m+8n=156 | | 5(x+4)/4=3x-1 | | 5(x+4)/4=3x+1 | | X+(3x+2)=26 | | Y=1/2x-8 | | x-(1+x)+2x=-x+1 | | -11.1=8.1+v/6 | | 375=900-300p | | 2-sec^2(X)=2tan^2(X) | | T/8=13 | | 4x-6*-2=15 | | W^2-6w-66=0 | | 2log(x-1)=5log(y+2) | | (4*5)/5+4=c | | logx+3logy=0 | | 5*4/5+4 | | (10n+10)-10=10 | | 3*-4-6/x=12 | | X^4+4.33X^3-10.34X^2-54.35X-51.67=0 | | 10n+10-10=10 | | 4s-3t=Ifors | | -2x+3x=-15 | | w(3w+2)-2(w^2-8)=w(w+5)-6w+7 | | H+3/4=78 | | 3x^2+x=-11x | | 6/x=3/5 | | 5+2*x=2*x+5 | | 5+2*x=5+(2x) | | T+5=23 |